DARK TOURISM - NEW FORM OF TOURISM IN ROMANIA - Rabontu Cecilia Irina (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
It is discussing,increasingly more often, in contemporary tourism, about new elements that enhances the appearance and development of new forms of tourism, including dark tourism which is based on the increasingly desire of modern tourist to achieve spiritual journeys, which have as attractions- deaths, disasters, atrocities, torture methods and other such issues. This subject has awoke our interest because we can find in Romania demand for this form of tourism but also various possibilities to use it in Romanian tourist circuits and also in the development of authentic tourism products with this subject. For Romania, this new form of tourism showed interest to academic research and to media, but in tourism literature we find a vacuum of information, being quite difficult to identify and label as dark tourism product a particular tourist site, a certain attraction or exhibition associated with death and dark, sinister and frightening elements, but we will try to discover certain components of this kind in Romanian tourism products.